Ozone Plasma Nanobubble (OPN) Reactor Combined with Coagulation-Flocculation Process: A Promising Technology for Leachate Treatment - Zahra, Habiibatuz; Azzahra, Ken; Putri, Azizka Inneke; Luvita, Veny; Bismo, Setijo (Indonesian Journal of Chemistry, 2024)
According to World Bank data, approximately 2.01 billion tons of urban waste is produced annually, with approximately 33% of waste being improperly managed, leading to concentrated and toxic leachate. This poses a global challenge due to its varied characteristics influenced by climate, landfill age, and waste composition, resulting in groundwater and surface water pollution with severe impacts on human health, ecosystems, and biodiversity, necessitating stringent treatment measures. To address this, a study integrated coagulation-flocculation and advanced oxidation processes (AOPs) using a dielectric barrier discharge (DBD) ozone plasma nanobubble (OPN) reactor to degrade leachate. Gas flow rate, plasma voltage, and gas sources are variated. This research uses O2 or air as a gas source that produces plasma. The leachate is fed into the DBD reactor, so the bubble will burst and produce further ROS. Optimal results were observed after 60 min, with oxygen gas feed reducing total suspended solids (TSS), chemical oxygen demand (COD), and biological oxygen demand (BOD) by 100, 93.93, and 74.12%, respectively, alongside a decrease in pH. This study indicates the promising potential of this technology for leachate treatment and demonstrates the potential for nitrate production using both types of gas feed.